Determinan Penghentian Premi (Lapse) dalam Industri Asuransi Jiwa Prudential: Tinjauan Dari Sisi Literasi Keuangan dan Kondisi Ekonomi Rumah Tangga - Cinta Aisyahtul Kubra; Isnaini Harahap; Andri Soemitra (Jurnal Riset Akuntansi, 2026)
This study aims to analyze the determinants of policy lapse behavior among policyholders of PT Prudential Life Assurance in Medan. The research employs a descriptive qualitative approach involving 10 policyholders selected purposively based on their experience of policy lapse. Data were collected through in-depth interviews, observations, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that policy lapse is a multidimensional phenomenon influenced by interconnected economic, cognitive, and service-related factors. Household financial pressures, declining income, and increasing living expenses encourage policyholders to prioritize essential needs over insurance premium payments. In addition, limited financial literacy leads many policyholders to perceive insurance primarily as a financial burden rather than a long-term risk management instrument. Dissatisfaction with agent services, including inadequate communication, insufficient policy education, and weak after-sales assistance, further reduces policyholders’ commitment to maintaining active coverage. The study also finds that policyholders frequently regard insurance as a last-resort liquidity source, supporting the Emergency Fund Hypothesis, whereby policies are surrendered or allowed to lapse during periods of financial distress to meet urgent household needs. This research concludes that policy lapse is often a pragmatic response to economic uncertainty rather than merely a consequence of unwillingness to pay premiums. Therefore, improving product transparency, strengthening financial literacy, and enhancing the role of insurance agents as proactive, solution-oriented financial advisors are essential strategies for increasing long-term policy persistence and customer retention.